Development of a Reference Book on the Charm of Macroscopic Fungi in Lubuklinggau Based on Exploration of the Surrounding Nature to Strengthen SDG-Oriented Learning - Reny Dwi Riastuti; Mareta Widiya (Jurnal Penelitian Pendidikan IPA, 2025)
The teaching of plant taxonomy in Indonesia still faces limitations in the availability of teaching materials that are relevant to local conditions, requiring the development of contextual learning resources that are appropriate to local potential and meaningful. This study addresses the scarcity of specialized, locally relevant teaching materials for the Lower Plant Taxonomy course. We developed a reference book, "The Charm of Macroscopic Fungi in Lubuklinggau," to serve as a valid, practical, and effective teaching aid. This resource uses a nature exploration approach to connect students with local biodiversity, reinforcing learning aligned with Sustainable Development Goals (SDGs), specifically targets 4 (Quality Education) and 15 (Life on Land). The research employed a Research and Development (R&D) method using the 4-D model (Define, Design, Develop, Disseminate). Expert validation confirmed the book's quality, with subject matter experts rating it "excellent" (score: 34), and media and language experts rating it "good" (scores: 39 and 34, respectively). Pilot testing on students showed the book's effectiveness in improving understanding, with normalized gain (N-gain) scores predominantly in the moderate to high categories. Our findings demonstrate that integrating local ecological potential and active learning strategies, such as nature exploration, is an effective way to improve biology education while promoting sustainability